Exploring sport and exercise psychology - Van Raalte, Judy L.; Brewer, Britton W. (Washington, D.C. American Psychological Association, 2014)
This book provides a comprehensive overview of the field of sport and exercise psychology, including common interventions for performance enhancement and health and well-being.
Introduction to Sport and Exercise Psychology / Britton W. Brewer and Judy L. Van Raalte -- -- I. Performance Enhancement -- -- Comprehensive Sport Psychology Services / Harriet D. Speed and Mark B. Andersen -- Goal Setting in Sport and Exercise : Research to Practice / Robert S. Weinberg -- Imagery Training for Peak Performance / Daniel Gould, Dana K. Voelker, Nicole Damarjian, and Christy Greenleaf -- Cognitive Strategies in Sport Psychology / Aidan Moran -- Intensity Regulation and Sport Performance / Gregory S. Wilson and Jim Taylor -- Modeling : Is What You See, What You Get? / Penny McCullagh, Diane Ste-Marie, and Barbi Law -- -- II. Promoting Well-Being -- -- Exercise Initiation, Adoption, and Maintenance in Adults : Theoretical Models and Empirical Support / Beth C. Bock, Sarah E. Linke, Melissa A. Napolitano, Matthew M. Clark, Ronnesia B. Gaskins, and Bess H. Marcus -- Promotion of Physical Activity in Communities : Public Health Psychology of Physical Activity / David A. Dzewaltowski -- Clinica Applications of Exercise Therapy for Mental Health / Kate F. Hays and Wesley E. Sime -- Counseling Interventions in Applied Sport Psychology / Albert J. Petitpas and Taunya Marie Tinsley -- Teaching Life Skills Through Sport : Community-Based Programs / Tanya Forneris, Kathryn A. Conley, Steven J. Danish, and Lauren M. Stoller -- -- III. Clinical Issues -- -- Measurement in Sport and Exercise Psychology / Selen Razon and Gershon Tenenbaum -- Psychopathology in Sport and Exercise / Britton W. Brewer and Trent A. Petrie -- Referral Processes in Sport Psychology / Judy L. Van Raalte and Mark B. Andersen -- -- IV. Working With Specific Populations -- -- Psychological Interventions in Youth Sports / Ronald E. Smith and Frank L. Smoll -- Helping Intercollegiate Athletes In and Out of Sport / Scott B. Martin and Mark B. Andersen -- Working With Elite Athletes / Patrick H.F. Baillie, Henry Davis IV, and Bruce C. Ogilvie -- Diversity in Sport / Stephen P. Gonzalez, Ariane L. Smith Machin, and Karen D. Cogan -- -- V. Professional Issues -- -- Penny McCullough, John M. Noble, and Steve Portenga -- Certification in Sport and Exercise Psychology / Samuel Zizzi, Leonard Zaichkowsky, and Frank Perna -- Incorporating Sport and Exercise Psychology Into Clinical Practice / Kate F. Hays and Jack J. Lesyk -- Ethics in Sport and Exercise Psychology / James P. Whelan, Maggie Hill, Meredith Ginley, and Andrew W. Meyers.
Includes bibliographical references and index.
Keywords: Sports -- Psychological aspects; Exercise -- Psychological aspects